Development of a Laravel-Based RSVP and QR Code Menu System for Atap Langit - Putri Elok Nazwah Azzurra (COREAI: Jurnal Kecerdasan Buatan, Komputasi dan Teknologi Informasi, 2026)
Atap Langit is a culinary business where reservation (RSVP) and menu services play a vital role. However, managing customer data, reservation schedules, and physical menus manually has led to recording errors, scheduling irregularities, delayed service, and inefficient data management. To solve these issues, this study proposes a web-based RSVP and QR Code Menu system built with the Laravel framework. The system digitizes and integrates reservation recording, customer management, and menu presentation, allowing customers to book online and view menus via mobile devices for a more practical and efficient experience. The research aims to improve reservation efficiency, minimize errors, speed up information delivery, and enhance overall service quality and customer satisfaction. Adopting a Waterfall development methodology (requirements analysis, system design, implementation, testing, and maintenance), data was gathered through observation, interviews, and documentation. The study hypothesizes that this Laravel-based system significantly improves work efficiency, data accuracy, and service quality.